Validity and reliability of force-velocity outcome parameters in flywheel squats - Spudic, D.; Smajla, D.; Sarabon, N. (Journal of Biomechanics, 2020)
Our study was designed to check the reliability of force-velocity (F-v) relationship outcome measures using flywheel (FW) squats. The main objectives at the primary level were to test intra-session reliability of mechanical parameters for ten equidistant FW loads, and at the secondary level, to test reliability and validity of the F-v relationship outcome measures in case any possible reduction in used loads and number of loads - compared to the 10-load method as a reference - is administered. Twenty-six subjects performed two sets of five squats with FW loads in the range 0.025-0.25 kg·m2. Averaging six consecutive repetitions obtained ICC2.k > 0.9 for mean force and mean velocity results. Consecutively averaged parameters at the primary level showed excellent inter-set reliability (ICC2.1 > 0.9). The inverse F-v relationship was strong (R2 = 0.96). At the secondary level, Bland-Altman statistics showed decreasing bias and limits of agreement in combination with more loads. Theoretical maximal force and power showed smaller bias as F-v slope and theoretical maximal velocity for three loads or more. Four loads (0.025, 0.075, 0.225 and 0.25 kg·m2) lowered bias to a 5% in relation to the reference F-v slope. In conclusion, six repetitions are required to obtain trustworthy force and velocity results. The results will contribute to standardising the methodology for assessing the mechanical capacities of leg muscles using FW resistance. Moreover, assessing individual F-v profile with reduced protocol may be a less fatiguing tool for prescribing exercise intensity and for assessing training adaptations.